MODEL PEMBELAJARAN ANTAR-LEVEL PADA CREDIT UNION BEREROD GRATIA - Wilfridus B. Elu (Lembaga Administrasi Negara, 2018)
This case study is intended to describe the inter-level learning process at the Bererod Gratia Credit Union (CUBG) Jakarta and its characteristics based on the concept of inter-level learning in the organization and oriented to the strategic renewal developed by Crossan, Lane, and White (1999), which are learning between individual, group, and organizational levels through 4I: Intuiting, Interpreting, Integrating, Institutionalizing. Also described are the implications of organizational learning on corporate governance. The study was conducted on learning in solving problems of negative results case in the Bintaro Service Place (TP) and loan decisions that must involve the Head Office. Key informants consist of credit staff, Head of Office, and Committee members at Bintaro TP and General Manager at Head Office. The results show that the inter-level learning process in CUBG has a dynamic balance between learning for innovation and change (exploration) with learning for standardization for management certainty (exploitation). Learning is also holistic and includes single-loop learning to triple-loop learning. One important implication of corporate governance is the increasingly entrenched culture of check and balances at various levels of the organization. Communication centrality in learning requires the development of generative change capabilities at every level of the organization to ensure the continuity of transformation is in balance with the development of governance to maintain organizational integrity.Keywords: Organizational Learning; Inter-level Learning, Corporate Governance